2011
DOI: 10.1177/1750481310390167
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a name? Stance markers in oral argument about marriage laws

Abstract: This study examines the relationship between person-referencing terms and attorney and judges' stances during oral argument in three US state supreme courts as each considered whether its existing state law could restrict marriage to one man and one woman. After reviewing past work on stancetaking and person referencing, I provide background on appellate oral argument and the three cases. Combining discourse analysis with simple quantitative coding, the study shows that attorneys' and judges' choices of terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…An obvious case is legal defence and prosecution teams where, at a gross level, the defence, for example, will be expected to take a negative stance toward the plaintiff. When studied in more detail, the defence and prosecution's stances during trials are revealed to be shifting and much more finely tuned than we might expect (Tracy ). News journalists, also at a gross level, orient toward a neutral stance toward parties that they are interviewing but are also then skilled at shifting stance by using the reported speech of others as representative of ‘the public’, which allows them to occupy a more clearly critical stance (Clayman ).…”
Section: Editing For Stance Using Multimodal Materialsmentioning
confidence: 82%
“…An obvious case is legal defence and prosecution teams where, at a gross level, the defence, for example, will be expected to take a negative stance toward the plaintiff. When studied in more detail, the defence and prosecution's stances during trials are revealed to be shifting and much more finely tuned than we might expect (Tracy ). News journalists, also at a gross level, orient toward a neutral stance toward parties that they are interviewing but are also then skilled at shifting stance by using the reported speech of others as representative of ‘the public’, which allows them to occupy a more clearly critical stance (Clayman ).…”
Section: Editing For Stance Using Multimodal Materialsmentioning
confidence: 82%
“…For example, Whitehead and Lerner (2009) demonstrate how employing membership categorization in conversation reproduces the social organization of race. Tracy (2011), in her turn, shows the relationship between person-referencing terms and attorneys and judges' stances toward gay parties and same-sex marriages. The judges and the attorneys used these terms to influence the participants' understanding of what the real issue is and, consequently, the outcome of the case.…”
Section: Interactional Functions Of Referringmentioning
confidence: 97%
“…Oral arguments have the participatory and open‐ended quality of the trial interactions, but also the enhanced abstraction and somewhat philosophical insulation of the appellate opinions. For example, like trial participants who compete to frame an alleged victim of manslaughter as a “baby” versus a “fetus” (Danet ), participants in various sexual‐orientation cases' oral arguments have traded conversationally in evolving cultural connotations of “gay” versus “homosexual” (Tracy ). But, unlike the many trials where actors involved in the underlying events also speak in court, appellate participants cannot attach such person‐referents to immediate interlocutors (cf.…”
Section: The Broader Contextmentioning
confidence: 99%